The Impact of Media Type on the Advertising Effectiveness on Mobile Social Media - Pan, Jieqi (2018)
The increasing popularity of mobile devices introduces a new way for companies and marketers to realise their goals of mobile marketing communications. The technical functions of mobile applications make lives more convenient. Especially the social networking applications allow people communicate with each other at anytime and anywhere. It provides companies with new channels to reach their target market and customers. What factors can affect the advertising effectiveness on mobile social media apps becomes a topic with growing interest. Among the factors, the influence of media type is seldom researched. The purpose of this study is to explore whether media type can influence the advertising effectiveness in the context of mobile social media. In order to do so, an online survey was designed to collect the original data. Survey link was spread on WeChat and Weibo and finally 231 respondents from 12 cities in China composed the data set. The data was analysed by the STATA software. The research applied multiple analysis methods such as a comparison of mean value, independent T-test, one-way ANOVA, correlation analysis and regression analysis. The findings give some evidences that media type does have impact on advertising effectiveness on mobile social media. The findings also indicate some other facts. The first one is that the comparison of two media types shows more effectiveness in video ads than still picture ads. The other one is that the comparison of the consumers’ behavioural intentions to behave on mobile social media apps shows a higher probability of clicking the Like button than clicking the Share button or Commenting on the ads. This study offers insights for marketers who intend to use mobile social media for marketing communications to consider a choice of media type when advertising.